POTENSI TRIMIRISTIN BIJI PALA FAKFAK (Myristica argantea warb) DAN EKSTRAKSI KULIT BUAH NAGA MERAH SEBAGAI BAHAN ADITIF SABUN DALAM PENERAPAN KIMIA HIJAU: REVIEW ANALISIS - Isma Yanti Vitarisma; Atikah Atikah; Yudhi Utomo; Eli Hendrik Sanjaya (Jurnal Ilmu Lingkungan, 2022)
Fakfak nutmeg seeds contain 6% of essential oil and 11-34% of fat. Trimyristin contained in nutmeg seeds reaches 80%. The oil and fat content in the nutmeg seeds can be used as an ingredient for making soap, perfume and other industrial materials. Tools made of stainless steel can be used to distill the oil content in nutmeg seeds. Reflux system using ester which will then be purified using acetone and then tested again with gas chromatography to isolate and purify nutmeg essential oil. Extraction of anthocyanin pigments from red dragon fruit peel waste using maceration method using distilled water and 10% citric acid with a ratio of 1:6 which is a mixed solvent type. The test parameters used pH values and absorbance values were measured using spectrophotometry with the UV-Visible method to determine and analyze the brightness level of the anthocyanin red dye content. The results of the content of trimyristin which can be potential as a soap additive and can be tested for anti-bacterial and anti-fungal properties combined with the principle of green chemistry.